2020
DOI: 10.1007/s12520-020-01231-x
|View full text |Cite
|
Sign up to set email alerts
|

Piecing together a new mosaic: Gravettian lithic resources and economic territories in the Western Pyrenees

Abstract: To palliate the current scarcity of information about lithic raw materials in the Western Pyrenees during the Gravettian, the study of ten assemblages has explored the flint procurement patterns and economic organisation of the territory. The study was based on the macro- and microscopic analysis of the different lithic remains. A wide range of flint varieties were used, including some excellent rocks for knapping and others of poorer quality. This diversified catchment pattern was defined by the criteria of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These changes probably enhanced the progressive transition from residential to logistical mobility, leading to a better understanding of resource predictability by hunter‐gatherers. Interestingly, logistic features were possibly identified for Gravettian groups in the Northern Meseta (south of the study area), while residential features were identified for Gravettian groups in the Western Pyrenees (Calvo & Arrizabalaga, 2020), in an ecological and climatic context closer to our study area. Even though the Gravettian and the Northern Meseta are outside the scope of this work, the LGM and related perturbations of human ecological niches could have forced these populations to reorganise their subsistence strategies leading to important behavioural changes in the Solutrean onwards (Solich & Bradtmöller, 2017).…”
Section: Reconstructing Energy Regimesmentioning
confidence: 62%
See 1 more Smart Citation
“…These changes probably enhanced the progressive transition from residential to logistical mobility, leading to a better understanding of resource predictability by hunter‐gatherers. Interestingly, logistic features were possibly identified for Gravettian groups in the Northern Meseta (south of the study area), while residential features were identified for Gravettian groups in the Western Pyrenees (Calvo & Arrizabalaga, 2020), in an ecological and climatic context closer to our study area. Even though the Gravettian and the Northern Meseta are outside the scope of this work, the LGM and related perturbations of human ecological niches could have forced these populations to reorganise their subsistence strategies leading to important behavioural changes in the Solutrean onwards (Solich & Bradtmöller, 2017).…”
Section: Reconstructing Energy Regimesmentioning
confidence: 62%
“…These changes probably enhanced the progressive transition from residential to logistical mobility, leading to a better understanding of resource predictability by hunter-gatherers. Interestingly, logistic features were possibly identified for Gravettian groups in the Northern Meseta (south of the study area), while residential features were identified for Gravettian groups in the Western Pyrenees (Calvo & Arrizabalaga, 2020), in an ecological and climatic context closer to our study area.…”
Section: Reconstructing Energy Regimesmentioning
confidence: 69%
“…( 127 , 128 ) and Aitzbitarte III between 28,000 and 22,000 cal B.P. ( 129 ). Eyed needles make an early appearance in the archaeological record of North America, dated to ~14,000 cal B.P.…”
Section: Archaeological Evidencementioning
confidence: 99%
“…The case of open-air occupations, especially in the Gravettian, has been described above. Six camps, hunting posts or flint workshops are now known, which permits a fuller image of the use of the territory (Calvo, 2019; Arrizabalaga and Iriarte-Chiapusso, 2020; Calvo and Arrizabalaga, 2020). Indeed, although it is still difficult to conciliate the archaeological scale expressed in millennia with the historical scale of the groups or individuals who created the record, knowledge gained in the last decade has allowed us to consider the territorialisation of collectives.…”
Section: Human Resilience and Use Of The Resources In The Environmentmentioning
confidence: 99%